Bubbles in US regional house prices: evidence from house price–income ratios at the State level - Hu, Y.; Oxley, Leslie (Routledge, 2018)
We investigate the presence of bubbles in the US house price-income ratio at the State level by applying the recent time series based econometric test to data from January 1975 to December 2014. We find evidence of bubbles in several States in the 1980s (i.e. California, Hawaii, Massachusetts, New York, etc.), which coincides with some existing studies that investigate housing bubbles or booms and busts using a range of alternative approaches. Our results show the existence of a housing bubble that originates in the early 2000s and collapses in the mid-2000s in more than 20 States and the District of Columbia concluding that the bubbles of the 2000s were more widespread than the 1980s, which is of special interest and importance. Our results seem to be in agreement with the talk given by Alan Greenspan in 2005, who suggest no sign of a nationwide housing bubble but a lot of local bubbles. We also study the importance of the regression model specification with/without an intercept and the regression model with an intercept could lead to false-positive identification of bubbles.